Determining the economic value of trust - Newman, Claire Cathey (Kansas State University, 2016)
Trust has been considered an integral part of maintaining any successful business relationship, and without trust, a business transaction would likely not occur. While trust has been a necessary component of these transactions, there remains to be minimal research on if customers truly value trustworthiness in a sales representative. And if customers do indeed value a trusted relationship, little is known how sales representatives can best enhance these trusted relationships. The primary objective of this research was twofold; first the economic value of trust and its components was estimated in a loan officer and farmer relationship, and second, was identifying the most effective ways that loan officers or sales representatives can increase their own trustworthiness with farmers. An online survey distributed to Kansas farmers was composed of three main components; general trust section, a best-worst simulation, and a choice experiment section. The general trust section motivated respondents to think about their perceptions of trustworthiness. In a best-worst simulation, respondents indicated which statements most and least represented the four trust components. The last section prompted respondents to report the trust score of their current loan officer and ranked that loan officer against hypothetical loan officers. Using a rank-ordered logit, the willingness to pay (WTP) estimates were calculated, giving insight to the most valued components of trust. Results from the choice experiment show that farmers greatly value self-orientation far above the other three trust components. On average, farmers are willing to pay .90% interest rate for a loan officer to be very focused on them and their operation. For a very credible and a very reliable loan officer, farmers were willing to pay .80%. Intimacy, or strong connection between the loan officer and farmer, was a distant last with farmers only willing to pay .40%. In conclusion, Kansas farmers do place economic value on trust in a business relationship. Self-orientation was the most valued trust component, and sales representatives who want to deepen a trusted relationship should focus on bettering themselves. This paper will generate ample discussion as it is a significant contribution to the literature on trust in business relationships.
Keywords: Agriculutral Sales Representatives; FarmersTrust